Pengaruh Kepemimpinan Transaksional Kepala Ruangan terhadap Pelaksanaan Asuhan Keperawatan Perawat Pelaksana (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to determine the effect of head room transactional leadership on the implementation of nursing nurses' nursing care. The design of this study was Quasy Experiment with pre and post test design with control group. The results of the analysis of transactional leadership data have a significant effect on the implementation of nursing care in the intervention group with a p-value of 0,000